Hospitais de pequeno porte no SUS do estado de São Paulo - Dínio Vaz Mendes, José; Marcondes Cecilio, Mônica Aparecida; Rodrigues Lopes Osiano, Vera Lucia (BEPA. Boletim Epidemiológico Paulista, 2014)